Examining Mental Health Knowledge, Stigma, and Service Use Intentions Among Public Safety Personnel - Krakauer, Rachel L.; Stelnicki, Andrea M.; Carleton, R. Nicholas (Frontiers in Psychology, 2020)
Introduction: Public safety personnel (PSP; e.g., communications officials [e.g., 911 call center operators/dispatchers], correctional service employees, firefighters, paramedics, police officers) experience an elevated risk for mental disorders due to inherent work-related stress. Several programs have been designed to increase mental health knowledge, intending to reduce stigma, and increase mental health service help-seeking (e.g., resilience training); however, extant programs have not demonstrated sustained improvements for PSP mental health. The current study assessed levels of mental health knowledge, stigma, and service use intentions in a sample of Canadian PSP and compared trends to published estimates of mental health symptoms across PSP categories to inform future programming. Methods: PSP completed questionnaires assessing mental health knowledge, stigma against coworkers with mental illness, and professional service use intentions. Correlations among variables and one-way analyses of variance were conducted to assess differences among categories. PSP were categorized into six categories for comparison: communication officials, correctional workers, firefighters, municipal/provincial police, paramedics, and Royal Canadian Mounted Police (RCMP). Results: There were significant differences between categories for each variable. Correctional workers reported the most mental health knowledge, least stigma, and highest intentions to use mental health services, and the highest positive screens for mental disorders. Conversely, firefighters reported the lowest mental health knowledge, highest stigma, and lowest willingness to seek professional help, and the lowest prevalence of positive screens for mental disorders. Discussion: The results contrast previously hypothesized associations among mental health variables where education, stigma reduction, and help-seeking have been expected to improve mental health. The discrepant results offer potentially critical information for organizational policies to better support PSP. Individuals reporting mental health symptoms may be a more appropriate target audience for intervention strategies, given the possible, crucial role personal experience plays in increasing mental health knowledge, and ultimately, encouraging help-seeking.